Déficit habitacional brasileiro: análise das políticas habitacionais de baixa renda - Pepe Filho, João Renato (2018)
The main goal of the following dissertation is to analyze if Brazilian housing policies were, in fact, adherent to the goal of gradually reduce the housing deficit, or if as soon as they were put in action, and they have distorted their main goal. Regarding that, it is discussed in what measure were important those secondary goals, such as their use as a form of population control, in order to strengthen government force and because of the economic and social benefits obtained from the heating of the civil construction market, due to its big productive related chain (directs and indirect) and the great number of jobs created. Regardless of, another goal of this dissertation is to analyze in what measure the income inequalities (lack of a proper income distribution) is harmful to the success of housing policies in Brazil, discussing solutions that enable the reduction of this “financial distance” and highlighting some disabilities, like the tax system, which charges more the general consumption instead of the individual income. Will be analyzed in details the most relevant Brazilian housing policies, starting with “Sistema Financeiro da Habitação/Banco Nacional da Habitação”, and then focusing on the analyze of “Programa Minha Casa Minha Vida” – creation, apex and crisis